Autonomous device for application in late-phase hemorrhagic shock prevention. - Vlad Oncescu; Seoho Lee; Abdurrahman Gumus; Kolbeinn Karlsson; David Erickson (PLoS ONE)
Hemorrhagic shock (HS) is the leading cause of death for people with traumatic injuries. The onset of HS is correlated with marked changes in the plasma vasopressin levels and some studies indicate that administrating vasopressin in the bloodstream can help stabilize the situation. This situation calls naturally for the use of implantable devices for both the monitoring and treatment of HS. In this work, we present a self-powered hemorrhagic-shock autonomous integrated device (hemoAID) that continuously monitors vasopressin levels and releases vasopressin automatically when levels drop below a certain threshold. We demonstrate that the device can operate at physiological concentrations of vasopressin, in sheep serum, thus paving the way towards the development of an autonomous implantable device for HS prevention.